Hair Follicle Nevus with Sebaceous Hyperplasia: A Dermoscopic Observation - Kazutoshi Harada; Yuichiro Kato; Yukihiko Kato; Ryoji Tsuboi (Karger Publishers, 2015)
We herein report a case of hair follicle nevus, a rare hamartoma found on the face and showing follicular differentiation, which was associated with sebaceous hyperplasia. Dermoscopy of the lesion showed yellow globules surrounded by crown vessels/telangiectasias and scattered tiny hairs. Histopathological investigation revealed hyperplasia of the sebaceous glands and proliferation of well-differentiated vellus hair follicles. These pathological findings were thought to correspond to the yellowish globules and tiny hairs observed under dermoscopy. Hair follicle nevus associated with sebaceous hyperplasia is extremely rare; however, dermoscopic examination can suggest an appropriate diagnosis. The present case proved the diagnostic usefulness of dermoscopy for cutaneous tumors with hair follicular and sebaceous glandular differentiation.